Primary Hyperaldosteronism Due to Adrenocortical Adenoma: a Case Report - Tjokorda Gde Dalem Pemayun; Ridho Naibaho; Maretina W Wiyati; Ardy Santosa; Siti Amarwati (Acta Medica Indonesiana)
Primary hyperaldosteronism is an adrenal abnormality in which there is some degree of autonomy of aldosterone secretion. We report a case of thirty three years old Javanese female presented with uncontrolled hypertension, muscular weakness, cramps  and progressing shortness of breath during working for 6 years. She had history of hypertension since age 20. Her serum potassium level was always low that associated with inappropriate kaliuresis. Blood gas analysis revealed metabolic alkalosis. Sonography of the adrenal gland showed right hipoechoic architecture; CT scan of the abdomen confirmed an right adrenal tumor measured 4 cm in its greatest dimension. Endocrine evaluation revealed high plasma aldosterone concentration, suppressed plasma renin activity, aldosterone/renin ratio of 112 and confirmed the diagnosis of primary aldosteronism. She underwent unilateral adrenalectomy. Histopathological report from excised adrenal tumor were compatible to benign adrenocortical adenoma. The patient discharge home with well controlled blood pressure and normokalemia. No clinical symptoms was reported in follow-up.